2015
DOI: 10.1371/journal.pone.0121802
|View full text |Cite
|
Sign up to set email alerts
|

Social Communication in Mice – Are There Optimal Cage Conditions?

Abstract: Social communication is heavily affected in patients with neuropsychiatric disorders. Accordingly, mouse models designed to study the mechanisms leading to these disorders are tested for this phenotypic trait. Test conditions vary between different models, and the effect of these test conditions on the quantity and quality of social interactions and ultrasonic communication is unknown. The present study examines to which extent the habituation time to the test cage as well as the shape / size of the cage influ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…During social encounters mice typically emit more USVs when they are in physical contact with one another (Ferhat et al, 2015 ). Several studies have investigated how different contexts affect the emission of USVs in mice.…”
Section: Discussionmentioning
confidence: 99%
“…During social encounters mice typically emit more USVs when they are in physical contact with one another (Ferhat et al, 2015 ). Several studies have investigated how different contexts affect the emission of USVs in mice.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies [10,25,26], we conducted recordings without the devocalization of female encounters under natural conditions. Previous experiments suggested that most vocalizations are produced by the resident subjects and that the vocal contribution of female encounters is very limited in the male-female and female-female contexts [27][28][29].…”
Section: Settings and Procedures For Ultrasound Recordingsmentioning
confidence: 99%
“…One of the earlier Arid1b +/models reported by Celen et al, described longer call durations and reduced pitch frequency while our report focused on the standard parameter of call number 17 . While a large number of studies report these vocalizations play a significant role in pup retrieval, and pups' ability to thrive 74 , there is much debate about their function and their translational relevance in genetic mouse models, made using congenic inbred mice beyond the existence of the calls, especially since in mice these calls are innate over learned [75][76][77][78][79] . The number of call emissions as pups is known to be greater in outbred strains, differ across inbred strains, days of post-development, and cage conditions leaving numerous possibilities for the differing results.…”
Section: Discussionmentioning
confidence: 99%